PORTFOLIO TECHNOLOGY AS A MEANS OF FORMING PROFESSIONAL COMPETENCIES FOR FUTURE SOCIAL SPHERE WORKERS - Kononchuk, Antonina (Social work and education, 2018)
The article reveals the relevance of using new approaches and technologies to the formation of professional competences of future social workers in the process of professional training. The latest research on the definition of "portfolio" in the system of higher education analyzed. The portfolio presented as an innovative pedagogical technology for the formation of professional competences of future social workers. The principles, functions, essential characteristics of the technology are determined. The results of the research on the use of this technology in the process of training future social workers at Nizhyn Mykola Gogol State University within the framework of the study of educational disciplines presented. The possibility and prospects of the use of portfolio technology in preparing future employees of the social sphere in order to form professional competencies are considered.